2003
DOI: 10.1021/bi0301800
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nucleotide Sequence-Dependent DNA Binding of Poly(ADP-ribose) Polymerase in a Purified System

Abstract: The enzymatic transfer of ADP-ribose from NAD to histone H(1) [defined as trans(oligo-ADP-ribosylation)] or to PARP-1 [defined as auto(poly-ADP-ribosylation)] requires binding of coenzymic DNA. The preceding paper [Kun, E., et al. (2004) Biochemistry 43, 210-216] shows that oligonucleotides of dsDNA can serve as coenzymic DNA for PARP-1 trans- or auto-modification activity. Results of DNA-protein binding (EMSA) experiments reported here demonstrate that short DNA oligonucleotides containing the 5'-TGTTG-3' nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…Short-patch repair of DNA single-strand breaks is initiated by poly(ADP-ribose) polymerase-1 (PARP1) -a multi-domain enzyme activated by binding of its N-terminal DNA-binding domain (DBD) to DNA breaks [1][2][3][4][5] . Activated PARP1 utilises NAD + to Correspondence to: Andreas G. Ladurner; Laurence H. Pearl; Antony W. Oliver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-patch repair of DNA single-strand breaks is initiated by poly(ADP-ribose) polymerase-1 (PARP1) -a multi-domain enzyme activated by binding of its N-terminal DNA-binding domain (DBD) to DNA breaks [1][2][3][4][5] . Activated PARP1 utilises NAD + to Correspondence to: Andreas G. Ladurner; Laurence H. Pearl; Antony W. Oliver.…”
Section: Introductionmentioning
confidence: 99%
“…We have now determined the crystal structure of the human PARP1-DBD bound to a DNA break. Along with functional analysis of PARP1 recruitment to sites of DNA damage in vivo, the structure reveals a dimeric assembly whereby ZnF1 and ZnF2 domains from separate PARP1 molecules form a strand-break recognition module that helps activate PARP1 by facilitating its dimerization and consequent trans-automodification.Short-patch repair of DNA single-strand breaks is initiated by poly(ADP-ribose) polymerase-1 (PARP1) -a multi-domain enzyme activated by binding of its N-terminal DNA-binding domain (DBD) to DNA breaks [1][2][3][4][5] . Activated PARP1 utilises NAD + to Correspondence to: Andreas G. Ladurner; Laurence H. Pearl; Antony W. Oliver.…”
mentioning
confidence: 99%
“…Such a sequence could be part of the genome of retrotransposable elements. The ability to bind sequence TGTTG has been previously reported for mammalian PARP1 (32). Sequence TGTTG is known to be an evolutionarily conserved flanking sequence for many retroviral and retrotransposable elements with long terminal repeats, such as copia and gypsy in Drosophila.…”
Section: Zn-finger Domain 1 Is Necessary For the Silencing Of Retrotrmentioning
confidence: 91%
“…Studies with PARP-1-deficient cells and animals have revealed diverse functions of PARP-1, including roles in anti-recombination and genomic instability, DNA replication, regulation of telomere function and transcriptional regulation (Simbulan-Rosenthal et al, 1999;Smulson et al, 2000;Cayuela et al, 2001). Although no consensus DNAbinding sequence for PARP-1 has been established, the ability of PARP-1 to bind DNA in a sequence-specific manner was demonstrated by Huang et al (2004), where PARP-1 preferentially bound to DNA oligonucleotides containing the 5 0 -TGTTG-3 0 nucleotide sequence motif (Simbulan-Rosenthal et al, 2003). PARP-1 has also been shown to activate the human T-cell leukemia virus type I Tax-mediated transcription in murine lymphocytic leukemia cells through sequence-specific binding to the Tax-responsive element TTGACGACAA (Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%